FREEDOM OF EXPRESSION SEEN THROUGH LYRICS IN RICH BRIAN AND NIKI’S SONGS - Puspitarini, Diana (International Journal of Humanity Studies (IJHS), 2024)
Music is not only used as a tool to entertain people but also could be used as a medium to express the ideas of the songwriter or the singer. They could deliver the arguments that they are trying to tell not only to their fans but also to the other people. In this research, the writer wants to see the ideas that Rich Brian and NIKI are trying to express through their songs. The writer uses semiotics to get the data from Rich Brian and NIKI’s songs, especially the lyrics. In this research, the writer finds that Rich Brian and NIKI are expressing their arguments about issues that are still happening now. They are delivering their opinion through their lyrics to remind people. However, the writer also sees that through the lyrics, Rich Brian and NIKI are also trying to show their support for the issues that still happen.